Asian maritime power in the 21st century strategic transactions : China, India, and Southeast Asia - Sakhuja, Vijay (Institute of Southeast Asian Studies, 2011)
Maritime power has been a key defining parameter of economic vitality and geostrategic power of nations. The first decade of the twenty-first century has witnessed the rise of China and India as confident economic powers pivoting on high growth rates, exponential expansion of science, technology and industrial growth